2023
DOI: 10.7759/cureus.34858
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing Ferrous Sulfate and Iron Sucrose in Iron Deficiency Anemia in Pregnancy

Abstract: Introduction: Anemia among pregnant women is one of the major health concerns for healthcare workers. The management becomes a concern in the pregnancy where the question arises of which is better the intravenous iron sucrose or the oral ferrous sulfate tablets. To answer this, a randomized control trial comparing both the treatment options in a tertiary care government hospital was set up in the hilly terrains of India. This study discusses the effectiveness and practical aspect of using both, which seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Randomization process was detailed in 22 studies 18 , 19 , 54 73 , while insufficient information was available from ten studies 74 83 , no information from two studies 84 , 85 while only one study reported the selection through non-random allocation sequence 86 . Allocation concealment was described adequately using opaque envelopes in 12 studies 18 , 55 , 60 , 62 – 66 , 68 , 69 , 72 , 76 , while remaining did not indicate allocation concealment in their studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Randomization process was detailed in 22 studies 18 , 19 , 54 73 , while insufficient information was available from ten studies 74 83 , no information from two studies 84 , 85 while only one study reported the selection through non-random allocation sequence 86 . Allocation concealment was described adequately using opaque envelopes in 12 studies 18 , 55 , 60 , 62 – 66 , 68 , 69 , 72 , 76 , while remaining did not indicate allocation concealment in their studies.…”
Section: Resultsmentioning
confidence: 99%
“…Blinding at patient level and provider level was not always feasible owing to different routes of administration. 17 studies did not mention about blinding or open-label in their studies 54 , 57 , 59 , 61 , 62 , 64 , 65 , 70 , 72 , 74 – 76 , 78 , 79 , 81 , 82 , 85 ; 13 studies were open-label trials 19 , 56 , 58 , 63 , 66 , 67 , 69 , 71 , 73 , 77 , 80 , 83 , 86 . Two studies reported blinding of data analysts or statisticians 60 , 68 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations